Historical Reason in the History of Philosophy - Ruiz Fernández, Jesús (Anales del Seminario de Historia de la Filosofía, 2011)
The current article aims to study the circumstantial e historical character of Ortega y Gasset’s Philosophy, organising the multiple dispersed data in his works. Philosophical literature has thought over the term vital reason a lot. However, it can be disappointingly observed that the most important issue hardly appears in its explanations. With it, Ortega meant, above all, that even in his there is no definitive philosophy. Consequently, the reason, the philosophy is alive, which does not mean that we are always the same, since Philosophy is more and more experienced: there is progress, complexity increases.
Keywords: circumstance; history of philosophy; Ortega y Gasset; historical reason.